(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives:- To assess and compare the effectiveness of strengthening and strengthening with stretching in patients with nonspecific low back pain Methodology:- There were total 40 patients with low back pain in the study. This study was done to find and compare the effect of strengthening and strengthening with stretching in patients with nonspecific low back pain. The patients were assessed with Visual Analogue Scale for pain and Manual Muscle Testing for the strength before and after 12 weeks of treatment. Result: Strengthening and stretching of the muscles has effect on the pain reduction as well as strength of the muscles in patients with nonspecific low back pain. Conclusion: On the basis of the result of this study, it was concluded that the strengthening and stretching of the muscles has effect on the pain reduction as well as strength of the muscles in patients with nonspecific low back pain